PILLARS OF MADRASAH QUALITY MANAGEMENT IN THE NEW NORMAL ERA - Amini Amini (Proceeding International Seminar of Islamic Studies, 2021)
This article aims to systematically describe the quality management pillars of madrasas in the new normal era which need to be understood so that the education service process in the new normal era, especially madrasas, still meets quality management standards. A review is needed related to the pillars of madrasah quality management so that later the management of these educational institutions can provide educational services with a planned and organized and controlled process so that they are in accordance with the results and objectives that have been set.Keyword: Pillar, Quality Management, Madrasa, New Normal